Hubungan Tingkat Pengetahuan dan Pola Asuh Orang Tua dengan Perkembangan Anak Prasekolah di Kelurahan Lubuk Buaya Padang Tahun 2019 - Wulandari Defera; Aprizal Ponda; Yussie Ater Merry (Jurnal Sehat Mandiri, 2021)
Data from the Padang City Health Service 2017 from 23 Puskesmas in Padang City, Lubuk Buaya Health Center 60% of the highest deviations in child development. One of the factors that influence it is the knowledge and parenting style of parents. The purpose of the study was to determine the relationship between the level of knowledge and parenting styles of parents with the development of preschool children in Darul Falah Kindergarten, Lubuk Buaya Padang Village in 2019. The type of research is an analytical survey with a cross-sectional design. The population is all parents and preschool children in Darul Falah Kindergarten as many as 50 people, the sampling technique is the total population. Collecting data using a questionnaire. Data analysis with univariate and bivariate using Chi-Square. It was found that 36% of preschool children's development was not appropriate, 26% of respondents had poor parental knowledge, 34% of parenting styles were at risk. The relationship between the respondent's level of knowledge with child development and the relationship between parenting patterns and child development obtained p value = 0.000 (p <0.05). There is a relationship between the level of knowledge and parenting patterns of parents with the development of preschool children in Darul Falah Kindergarten, Lubuk Buaya Padang Village in 2019. It is hoped that health workers will socialize stimulation of child development with counseling and preschool health promotion for parents.